Drosophila Cep135/Bld10 maintains proper centriole structure but is dispensable for cartwheel formation. - Roque, H; Wainman, A; Richens, J; Kozyrska, K; Franz, A; Raff, J (2012)
Cep135/Bld10 is a conserved centriolar protein required for the formation of the central cartwheel, an early intermediate in centriole assembly. Surprisingly, Cep135/Bld10 is not essential for centriole duplication in Drosophila, suggesting either that Cep135/Bld10 is not essential for cartwheel formation, or that the cartwheel is not essential for centriole assembly in flies. Using electron tomography and super-resolution microscopy we show that centrioles can form a cartwheel in the absence of Cep135/Bld10, but centriole width is increased and the cartwheel appears to disassemble over time. Using 3D structured illumination microscopy we show that Cep135/Bld10 is localized to a region between inner (SAS-6, Ana2) and outer (Asl, DSpd-2 and D-PLP) centriolar components, and the localization of all these component is subtly perturbed in the absence of Cep135/Bld10, although the ninefold symmetry of the centriole is maintained. Thus, in flies, Cep135/Bld10 is not essential for cartwheel assembly or for establishing the ninefold symmetry of centrioles; rather, it appears to stabilize the connection between inner and outer centriole components.